Komplikasi Nyeri dan Perdarahan Pasca Sirkumsisi Metode Klem - Resa Budi Deskianditya; Anis Kusumawati; Yuhantoro Budi Handoyo Sakti; Naura Faisa Adiyanti; Sabrina Diva Wulandari (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract: Circumcision is a minor surgery procedure that provides several benefits and is closely related to religious life.  Currently there are various methods in the action of circumcision.  The incindence of complication related to circumcision is low, but various variations of methods can affect complications.  The aim of this study is to present data on the incidence of pain and bleeding complication post clam method circumcision, as well as the factors associatd with both complications.  This study is an observational analytic study with a cross-sectional method, with the research subject is medical record data at Klinik Rumah Sunatan Purwokerto for the period January 2017 – August 2020 which meets the inclusion criteria and excluded from exclusion criteria.  Data were collected and performed bivariate analysis of independent variables to complications of pain and bleeding using the Spearmen method for numerical variables and Chi square for nominal and ordinal variables, and follow up with the backward logisitic regression test.  There were 153 medical record data met the criteria, with 47.7 % pain complication and 38.6 % bleeding compllication.  Multivariate test showed a significant relationship between aged and pain (p = 0.039; B = -0.155) and bleeding complication (p = 0.003; B = -0.202), glans adhesions with pain (p = 0.007; B = 1.295) dan bleeding complication (p = 0.005; B = 1.346), and narrow prepucium and pain (p = 0.002; B = 1.294) and bleeding complication (p = 0.003; B = 1.200).  The conclusion of this study is the frequency of pain and bleeding complication were 47,7 % and 38,6 % respectively, and there was a significat relationship between age, glans adhesions, and narrow prepucium with pain and bleeding complications.